JBiclustGE: Java API with unified biclustering algorithms for gene expression data analysis - Rocha, Orlando; Mendes, Rui (Knowledge-based systems, 2018)
Over the last years, comparative studies of biclustering algorithms have been described in the literature, showing that a variety of programming languages were used in their development. Because of this fact, many researchers have difficulty using some of these methods, since it is necessary to setup an environment for running a given algorithm or to have some programming skills in order to compile it. We present a new Java API for biclustering analysis in the context of gene expression data, allowing the use of 21 biclustering algorithms, in a single application. It is freely available at https://jbiclustge.github.io as an open source framework.